Impactos da regulação financeira, a partir de 2000, na estrutura e no desempenho do setor bancário brasileiro - Faria, Débora Campos de (2018)
This paper aims to identify how does regulation affect comercial banks profitability and market structure, from the perspective of the Structure-Conduct-Performance paradigm and Theory of Economic Regulation. Panel data analysis were used containing all banks that operated with commercial portfolio between 2000 and 2017. To treat banking performance, it was used as dependent variable the return on equity (ROE). The Herfindahl-Hirschman index (HHI) was used as proxy to analyse market structure. As independent variables, in addition to those related to bank efficiency and macroeconomic environment, traditionally addressed by the empirical economic literature, variables related to government regulation were included. The results point out that Targeted Credit negatively affects bank’s profitability. Despite of this, variables related to regulation, such as Compulsory Deposit, Targeted Credit and relevant regulations with potential to create barriers to entry (treated in models as dummy variables), were statistically significant, positively impacting market’s concentration levels. Data also suggest that although it does not directly affect market’s profitability, regulation indirectly influences it by contributing to a greater market concentration.